Development of an eco-friendly composite based on geopolymer matrix produced with fired clay brick powder and reinforced with natural fibers - Silva Mondragón, Guido Leonardo (2018)
Current construction industry is responsible for a large amount of greenhouse gas emissions due to the widespread use of building materials with high-embodied energy such as ordinary Portland cement-based materials and steel. Therefore, this thesis presents the development of a new eco-friendly building material based on a geopolymer matrix produced with Fired Clay Brick Powder (FCBP) and reinforced with natural fibers as a low CO2 alternative for the traditional building materials. With this purpose, a review of recent advances in the application of geopolymer composites and geopolymers reinforced with natural fibers in the construction industry were first presented. This review covers two major eco-friendly materials for construction: first, geopolymers obtained from industrial by-products and waste materials, such as fly ash, ground granulated blast furnace slag, construction and demolition wastes and main tailings; and second, natural fibers used as reinforcement for geopolymer composite materials. Literature review allowed the definition of morphology, size, and the molar ratio of SiO2/Al2O3 in the raw material, together with the alkaline solution/solid ratio, NaOH concentration, SiO2/M2O molar ratio in the total alkaline solution and the curing conditions as key parameters in the formulation of geopolymers. It has been also found that the type, pre-treatment, amount and length of the natural fibers play an important role in the reinforcement of geopolymer matrices. Once key parameters of geopolymer composites production were identified, an attempt for the formalization of a methodology to improve the compressive strength of FCBP-based geopolymers is presented. The tests allowed the definition of optimum conditions of the FCBP-based geopolymers formulation and curing conditions, which resulted in a cementitious matrix with high compression strengths of up to 37 MPa. Nevertheless, high-strength geopolymers evidenced a fragile behavior and low ductility similar to Portland cement-based materials. Therefore, the last part of the work was focused on the evaluation of natural cellulose fibers (jute and sisal) as reinforcement of FCBP-based geopolymers. The results indicated that jute and sisal fiber addition at the optimum content significantly improved the compressive, splitting tensile and flexural strength with respect to the unreinforced geopolymer matrix and lead to a shifting of the failure mode from a brittle to a more ductile failure in all mechanical tests.